The THE INFLUENCE OF DESTINATION IMAGE, TOURIST SATISFACTION AND TOURIST EXPERIENCE ON REVISIT INTENTION TO SERIBU NGALAU VILLAGE (NAGARI SISAWAH - Sulkaisi, Neffi; Nisha Selvia; Anita Citra Yeni; Citra Dwi Putri (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
This study aims to examine the influence of destination image, tourist satisfaction, and tourist experience on revisit intention to Seribu Ngalau Village (Nagari Sisawah), a growing ecotourism destination in Sijunjung Regency. Despite its natural attractions, the village faces challenges in retaining tourist interest and repeat visits. Using a quantitative approach, this research involved 150 respondents who had previously visited Seribu Ngalau Village. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS software. The results revealed that destination image positively and significantly affects both tourist satisfaction and tourist experience. Furthermore, tourist satisfaction and tourist experience have a direct and significant impact on revisit intention. These findings emphasize the importance of developing a positive destination image, enhancing tourist experiences, and fulfilling visitor expectations to build loyalty and encourage return visits. This study provides practical implications for destination managers and local government to design more sustainable and visitor-centered tourism strategies.